2009
DOI: 10.1111/j.1476-4431.2009.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cardiac output in neonatal foals by ultrasound velocity dilution and its comparison to the lithium dilution method

Abstract: When compared with LiDCO, the UDCO technique has acceptable clinical utility for measuring CO in healthy anesthetized newborn foals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The trending ability of the PulseCO was poor, with only 74% of ∆CO correctly tracked and wide RLOA. In another report comparing PulseCO to LiDCO in foals, the authors suggested good directional tracking, but a dedicated analysis of ∆CO data was not performed. The only report that described the analysis of trending ability in dogs calculated the concordance rate between the 2 continuous nonreference methods PulseCO and PiCCO .…”
Section: Discussionmentioning
confidence: 99%
“…The trending ability of the PulseCO was poor, with only 74% of ∆CO correctly tracked and wide RLOA. In another report comparing PulseCO to LiDCO in foals, the authors suggested good directional tracking, but a dedicated analysis of ∆CO data was not performed. The only report that described the analysis of trending ability in dogs calculated the concordance rate between the 2 continuous nonreference methods PulseCO and PiCCO .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac output measurement in veterinary patients is not routinely performed because of the invasiveness of currently validated procedures. 3,6 The clinical gold standard of CO measurement is the TDCO method, which requires the use of a pulmonary artery catheter. Use of pulmonary artery catheters is associated with major risks including development of arrhythmias, cardiac endothelial damage, infection, knotting of the catheter in the pulmonary artery, pulmonary thromboembolism, and pulmonary artery rupture.…”
mentioning
confidence: 99%
“…14,15 The UDCO technique was recently evaluated in anesthetized euvolemic neonatal foals (1 to 3 days of age). 6 There is, however, significant variation in CO values among horses of differing ages. Foals have high heart rates and CI values because of their high metabolic rates and immature sympathetic nervous system.…”
mentioning
confidence: 99%
“…In addition, indices of cardiac function derived from Doppler echocardiography have been found to be less repeatable than indices derived from 2‐D or M‐mode echocardiography in horses . It was recently shown that some volumetric echocardiographic methods provide an accurate and noninvasive estimate of CO in anesthetized neonatal foals . However, because of major differences in cardiac chamber sizes and inability to obtain apical views of the heart in adult horses, data generated from neonatal foals under general anesthesia cannot be directly extrapolated to adult horses.…”
mentioning
confidence: 99%
“…8 It was recently shown that some volumetric echocardiographic methods provide an accurate and noninvasive estimate of CO in anesthetized neonatal foals. 9 because of major differences in cardiac chamber sizes and inability to obtain apical views of the heart in adult horses, data generated from neonatal foals under general anesthesia cannot be directly extrapolated to adult horses. The purpose of this study was to assess and validate various transthoracic echocardiographic methods of measuring CO in standing adult horses over a range of CO by comparing results to the lithium dilution CO (LiDCO) method.…”
mentioning
confidence: 99%